2014
DOI: 10.3390/molecules19067072
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity of 2,3-Enopyranosyl C-Linked Conjugates of Genistein

Abstract: A series of glycoconjugates, derivatives of genistein containing a C-glycosylated carbohydrate moiety, were synthesized and their anticancer activity was tested in vitro in the human cell lines HCT 116 and DU 145. The target compounds 15-17 were synthesized by treating ω-bromoalkyl C-glycosides derived from L-rhamnal (1) with a tetrabutylammonium salt of genistein. The new, metabolically stable analogs of previously studied O-glycosidic genistein derivatives inhibited proliferation of cancer cell lines through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Other authors (Szeja et al, 2014 [ 16 ]) reported that genistein-2,3-Enopyranosyl conjugate D was active against human cell lines HCT-116 and DU-145 with IC 50 values of 2.25 and 4.64 µM, respectively [ 16 ]. In addition, in a different investigation, it was reported that conjugate E showed high activity over three ER-positive breast cancer cell lines, MCF-7, 21PT and T47D, with IC 50 values of 0.8, 0.9 and 0.9 μM respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors (Szeja et al, 2014 [ 16 ]) reported that genistein-2,3-Enopyranosyl conjugate D was active against human cell lines HCT-116 and DU-145 with IC 50 values of 2.25 and 4.64 µM, respectively [ 16 ]. In addition, in a different investigation, it was reported that conjugate E showed high activity over three ER-positive breast cancer cell lines, MCF-7, 21PT and T47D, with IC 50 values of 0.8, 0.9 and 0.9 μM respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that up to three of them have the α-configuration at the sugar unit anomeric carbon is worth emphasizing. However, the length of the linker between the sugar fragment and genistein appears to have an equally significant impact on the demonstrated cytotoxicity [ 167 ]. On the basis of the research results described so far using an in vitro cell model, it can be noted that genistein glycoconjugates containing the O -glycosidic or C -glycosidic linkage show in most cases significantly higher antiproliferative activity in comparison to the genistein parent compound.…”
Section: Glycoconjugatesmentioning
confidence: 99%
“…Compound 32 exhibited IC 50 value 2.28 and 4.64 μM whereas 33 showed IC 50 value 4.69 and 4.90 μM against HCT 116 and DU 145 cell lines respectively. Paclitaxel was used as reference drug that inhibited the proliferation of cell at low nanomolar concentrations [146] …”
Section: Semi‐synthetic Modification Of Genistein During the Period 2...mentioning
confidence: 99%